Multi-channel FSK inter/intra-chip communication by exploiting field-confined slow-wave transmission line - Chen, Qian (2020)
Using on-chip slow-wave transmission line (SW-TL) has paved a new way towards millimeter-wave (mm-wave) to terahertz (THz) low power and high speed inter-/intra-chip communications. This work presents an on-chip SW-TL featured by periodic comb-shape grooves with capability to strongly localize electric-field. A gradient groove structure is proposed to serve as the mode converter and performs the mode transformation between the quasi-TEM wave and the slow-wave with low return loss. Due to field confinement, when two SW-TL are only 2.4 μm apart, more than 19 dB crosstalk suppression is observed compared with two conventional TL with the same metal spacing. A dual-channel 160 GHz frequency-shift keying (FSK) transceiver is designed in 65 nm CMOS technology. The preliminary results show that by exploiting SW-TL as the silicon channel, the receiver can recover error-free 4 Gb/s dual-channel data, whereas the eye diagram of the transceiver using traditional transmission line (TL) is fully distorted. The transceiver consumes 36 mW DC power from a 1.2 V power supply.